EFEKTIVITAS PEMBELAJARAN ETNOMATEMATIKA MENGGUNAKAN PERMAINAN SIKIDOKA TERHADAP PEMAHAMAN KONSEP GEOMETRI BAGI SISWA SEKOLAH DASAR - Cornelia Amanda Naitili; Yulsy M Nitte (HINEF : Jurnal Rumpun Ilmu Pendidikan, 2023)
Abstract. Mathematics learning, chiefly in understanding geometric concepts taught in schools, still becomes elusive for elementary school students. This is as a result of the abstract characteristics of mathematics though the students' characters are at the concrete operational stage. Ethno-mathematics learning using sikidoka games can be an effort to overcome students’ difficulties in Mathematics learning because sikidoka games contain geometric concepts which are very directly related to students' lives. This study aims to determine the effectiveness of ethnomathematics learning using sikidoka games on understanding the concept of geometry for the third-grade students at SDN Unina. The sampling technique in this study is in the form of a saturated sample technique, so that the entire population used as research samples amounts 31 people, while data collection techniques applied in this study are test and documentation. Data analysis employs a paired sample t-test, but before that, a normality and homogeneity test are first carried out on the data that had been collected. Based on the data analysis, it is found that the results of the normality and homogeneity tests show that all data are normally distributed and homogeneous, while the results of the hypothesis test show that the significance value is 0.05 (0.016 <0.05), which means that ethnomathematics learning using sikidoka games has a positive and significant effect on the understanding of the concept of geometry for the third-grade students at SDN Unina. Abstrak. Pembelajaran matematika terkhususnya pada pemahaman konsep geometri yang diajarkan masih sering menjadi kendala bagi siswa sekolah dasar. Hal ini disebabkan karateristik matematika yang bersifat abstrak sedangkan karakter siswa berada pada tahap operasional kongkret. Pembelajaran etnomatematika menggunakan permainan sikidoka dapat menjadi upaya untuk mengatasi kendala tersebut karena dalam permainan sikidoka memuat konsep geometri serta sangat berkaitan langsung dengan kehidupan siswa. Tujuan penelitian ini adalah untuk mengetahui efektifitas pembelajaran etnomatematika menggunakan permainan sikidoka terhadap pemahaman konsep geometri siswa kelas III SDN unina. Teknik pengambilan sampel pada penelitian ini menggunakan teknik sampel jenuh, sehingga keseluruhan populasi tersebut dijadikan sampel penelitian yaitu berjumlah 31 orang sedangkan pengumpulan data dalam penelitian ini menggunakan tes dan dokumentasi. Analisis data menggunakan uji paired sample t-test namun sebelum uji t dilakukan uji normalitas dan uji homogenitas pada data-data yang sudah dikumpulkan. Hasil penelitian menunjukkan bahwa hasil uji normalitas dan homogenitas menunjukkan semua data berdistribusi normal dan homogen, sedangkan hasil uji hipotesis menunjukkan bahwa nilai signifikansi 0,05 (0,016 < 0,05) yang berarti bahwa pembelajaran etnomatematika menggunakan permainan sikidoka berpengaruh positif dan signifikan terhadap pemahaman konsep geometri bagi siswa kelas III SDN Unina.